Does the Mean Arterial Pressure Influence Mortality Rate in Patients with Acute Hypoxemic Respiratory Failure under Mechanical Ventilation? - Juarda Gjonbrataj; 김현정; 정혜인; 최원일 (Tuberculosis and respiratory diseases, 2015)
Background In sepsis patients, target mean arterial pressures (MAPs) greater than 65 mm Hg are recommended. However, there is no such recommendation for patients receiving mechanical ventilation. We aimed to evaluate the influence of MAP over the first 24 hours after intensive care unit (ICU) admission on the mortality rate at 60 days post-admission in patients showing acute hypoxemic respiratory failure under mechanical ventilation. Methods This prospective, multicenter study included 22 ICUs and compared the mortality and clinical outcomes in patients showing acute hypoxemic respiratory failure with high (75-90 mm Hg) and low (65-74.9 mm Hg) MAPs over the first 24 hours of admission to the ICU. Results Of the 844 patients with acute hypoxemic respiratory failure, 338 had a sustained MAP of 65-90 mm Hg over the first 24 hours of admission to the ICU. At 60 days, the mortality rates in the low (26.2%) and high (24.5%) MAP groups were not significantly different. The ICU days, hospital days, and 60-day mortality rate did not differ between the groups. Conclusion In the first 24 hours of ICU admission, MAP range between 65 and 90 mm Hg in patients with acute hypoxemic respiratory failure under mechanical ventilation may not cause significantly differences in 60-day mortality. Background In sepsis patients, target mean arterial pressures (MAPs) greater than 65 mm Hg are recommended. However, there is no such recommendation for patients receiving mechanical ventilation. We aimed to evaluate the influence of MAP over the first 24 hours after intensive care unit (ICU) admission on the mortality rate at 60 days post-admission in patients showing acute hypoxemic respiratory failure under mechanical ventilation. Methods This prospective, multicenter study included 22 ICUs and compared the mortality and clinical outcomes in patients showing acute hypoxemic respiratory failure with high (75-90 mm Hg) and low (65-74.9 mm Hg) MAPs over the first 24 hours of admission to the ICU. Results Of the 844 patients with acute hypoxemic respiratory failure, 338 had a sustained MAP of 65-90 mm Hg over the first 24 hours of admission to the ICU. At 60 days, the mortality rates in the low (26.2%) and high (24.5%) MAP groups were not significantly different. The ICU days, hospital days, and 60-day mortality rate did not differ between the groups. Conclusion In the first 24 hours of ICU admission, MAP range between 65 and 90 mm Hg in patients with acute hypoxemic respiratory failure under mechanical ventilation may not cause significantly differences in 60-day mortality. KCI Citation Count: 0